2012
DOI: 10.1002/cncr.27724
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide identification of Epstein‐Barr virus–driven promoter methylation profiles of human genes in gastric cancer cells

Abstract: BACKGROUND: Aberrant methylation of tumor-related genes has been reported in Epstein-Barr virus (EBV)-associated gastric cancers. This study sought to profile EBV-driven hypermethylation in EBV-infected cells. METHODS: The EBV-positive AGS gastric cancer cell line (AGS-EBV) and EBV-negative AGS cells were used in this study. DNA methyltransferase-3b (DNMT3b) activity was assessed by EpiQuick activity assay, and genome-wide DNA methylation profiles were assessed by methyl-DNA immunoprecipitation microarray assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
113
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 23 publications
6
113
0
Order By: Relevance
“…Apparently, variant 3 is differently affected by the methylation of DNA as not all the isoforms derived from this variant increased their expression under the same conditions, and it may indicate that variant 3 and the 498-bp isoform are benefited by the lack of DNA methylation in comparison with other derived isoforms. In general, these results are in agreement with previous reports, 15,28,29 suggesting that DNA methylation could underlie an isoform switch in IL-15RA. Whether the effect of DNA methylation on IL-15Ra gene is due to cis or trans methylation is not known as AZA acts as a general inhibitor of de novo methylation; however, Diniz et al found evidence of regulation on a CpG island located on the regulatory 5' upstream region and on the exon 1 of the IL-15Ra gene.…”
Section: Discussionsupporting
confidence: 94%
“…Apparently, variant 3 is differently affected by the methylation of DNA as not all the isoforms derived from this variant increased their expression under the same conditions, and it may indicate that variant 3 and the 498-bp isoform are benefited by the lack of DNA methylation in comparison with other derived isoforms. In general, these results are in agreement with previous reports, 15,28,29 suggesting that DNA methylation could underlie an isoform switch in IL-15RA. Whether the effect of DNA methylation on IL-15Ra gene is due to cis or trans methylation is not known as AZA acts as a general inhibitor of de novo methylation; however, Diniz et al found evidence of regulation on a CpG island located on the regulatory 5' upstream region and on the exon 1 of the IL-15Ra gene.…”
Section: Discussionsupporting
confidence: 94%
“…The process involves a series of tumor suppressor genes (eg, p14, p15, p16, APC, CDH, MGMT and PTEN), which result in uncontrolled cell growth. 20,21 Of note, although microsatellite-instable gastric adenocarcinomas are also associated with hypermethylation and silencing of genes (and their promoters) in a distinctive pattern. EBV gastric cancers having a more extensive pattern of methylation of promoter and non-promoter CpG islands.…”
Section: Discussionmentioning
confidence: 99%
“…6,23,24,28,29 This trend was also recorded in the Asian Cancer Research Group data set. 7 It has been suggested that the profound global DNA effects are responsible for the distinctive clinicopathologic features of EBV gastric cancers 20 including male predominance 9,30 and proximal location. 31 Notably, the purported younger age has not been confirmed by recent analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This subset of gastric carcinoma, 8 to 10% of cases, is more prevalent in Caucasian and Hispanic patients than Asians, and it shows no association with Helicobacter pylori infection (22). In these cases, EBV appears to play a direct oncogenic role through genome-wide alteration of promoter methylation (24), microRNA (miRNA) expression, and expression of genes involved in cell motility and transformation pathways (25). The integration status of EBV in gastric carcinoma remains poorly understood.…”
mentioning
confidence: 99%